Indonesian Online News: Where Does the Bias Go? - Ratnaningsih, Anastasia (Journal of Language and Literature, 2019)
The shift from printed articles to online articles makes online news even more important for us. This saying is also applied in Indonesia, as people in Indonesia have started to turn toward online news rather than printed ones. Due to the interest Indonesians have gathered toward online news, it is important for online news to be as objective as possible, as it becomes a primary source of information and the latest updates. For this reason, this research delves into the world of Indonesian online news to see how objective it is. This research uses Kompas.com as its subject of research, and propaganda model becomes the primary theory with critical discourse analysis (CDA) as its framework. Propaganda model uses ownership, advertising, sourcing, flak, and fear as aspects used to measure the mass media, in this case Indonesian online news. This research also uses ideology where power comes into play. Through propaganda model, ideology, and CDA, this research finds out that despite of the objectivity that is supposed to exist in Indonesian online news, in this research is Kompas.com, only subjectivity and bias can be seen from it. The bias and subjectivity stem from various aspects. Through propaganda model, this research finds out that those aspects are ownership, sponsorship, personal beliefs, and profit. Despite the fact that Kompas.com is supposed to be neutral, there is little neutrality in their articles, as their articles are generated based on the bias made by the aspects mentioned. Although this research only uses Kompas.com, Kompas.com becomes an example of how little objectivity Indonesian online news has. Being the source of information, it is expected to be objective and neutral. However, instead of being neutral, Indonesian online news is biased with certain factors affecting the way the news is written. Instead of having accurate and objective online news, it is written with bias and in non-neutral way.